Efficiency of Plant Active Compounds as Anti-Adhesion Factors for Clinical Candida albicans Isolates in vitro - Khairallah, Dhuha Hussein; Majeed, Majid Rasheed (Iraqi Journal of Science, 2020)
The aim of this study is the determination of the anti-adhesion activity of active compounds extracted from plants in the inhibition of adhesion ability of C. albicans that is used as a virulence factor for infection. Adherence to host surfaces is a primary factor in the colonization of human tissues by fungi, which can also adhere to the surfaces of medical devices and form biofilms. Medicinal plants possess therapeutic properties or beneficial pharmacological effects on the body. A total of one hundred samples were collected from female patients with vaginal infection in two hospitals in Baghdad city for three months. The fungi were isolated and identified by microscopic morphology, morphological features on culture media, and Vital Index of Traditional Environmental Knowledge (VITEK 2) System. Extraction and purification of plant active compounds, vasicine from Adhatoda vasica and gallic acid from Punica granatum L. , were performed. The active compounds were used as anti-adhesion factors and the minimum inhibition concentration (MIC) against Candida albicans was determined. We also used the antifungal drug fluconazole for comparison as a control. The results of vaginal discharge characterization of clinical samples showed that 30% of the infections are caused by fungi (100% were Candida albicans), 47% by Gram negative bacteria, and 23% by Gram positive bacteria. The results of MIC assays showed that the plant extract and the antifungal drug do not seem to have fungicidal effects on the isolates of C. albicans tested. The ability of C. albicans isolates for adhesion to the epithelial cells was detected by the calculation of the number of adherent C. albicans cells under light microscope. The activity of vasicin and gallic acid appeared to be approximately equal on the number of C. albicans adherent on epithelial cells. Vasicin concentration activity used in mg/ ml was higher than that used in Âµg/ ml, with less numbers of C. albicans adhered on epithelial cell. However, treatment with fluconazole showed that more than half of the number of C. albicans were non-adherent on epithelial cells when added to the suspension, in contrast to the control (C. albicans without the extracts or antifungal drug).